Students’ Problems in Pronouncing Non-Existing English Diphthongs in Indonesian Language - Anwar, Yasinta; Kalisa, Pasca (Language Circle: Journal of Language and Literature, 2020)
One of the difficulties in learning the English language faced by Indonesian students is how to pronounce English sounds correctly. For several Indonesian students, producing English diphthong sounds could be difficult especially English diphthong sounds which do not exist in Indonesian ([ɪə], [ʊə], [eɪ], [eə] and [oʊ]). This study investigated the Indonesian students’ problems English diphthong pronunciation. The objective of this study was to describe how well the English diphthong sounds are pronounced by the students and to find out the kind of errors that were mostly found in the pronunciation of students. The participants of this study were 35 students of the eleventh grade of SMK N 2 Salatiga. The instruments were the production test containing English diphthong sounds and interviews as additional data. In determining the achievement, the level of criterion by Tinambunan’s criterion was used. Based on the data analysis, the total average of the incorrect numbers of English diphthong sounds in pronunciation made by students was 69% which was categorized as fair. In addition to it, the kinds of errors mostly found in the students’ pronunciation English diphthong sounds were omission errors. According to the result of the interview, the causes of the errors were unfamiliarity of knowing English diphthong sounds, so the sounds of English appeared to pronounce with the closest Indonesian sounds.